AN ANALYSIS OF LANGUAGE IMPAIRMENT OF AUTISM IN LIFE, ANIMATED FILM - Abdul Kholiq; Dian Luthfiyati; Nur Dian Tamimih (Universitas Islam Lamongan, 2021)
The aims of this study were to find language impairment of autism in Life, Animated film. The autistic child in this film is the second son of Suskind Family This study the writer uses descriptive analysis techniques. The data of this study are the conversation of Life, Animated film. Data analysis techniques used in this study is transcription, classification and analysis. Data source was Life, Animated Film. This study only focused on language impairment. The result of this study shows that Owen language impairments are Owen was confused or needed a help if he have to answer but he was forgotten. His articulation sometimes can be fast or slow, especially when Owen talked with Emily, he articulated slower than usual. He often use word “great” because his vocabularies are low, he confused to understand other people, he was echolalia, his articulation is delay and he like something scripted, but he did not confuse in using pronoun and grammatical. Keywords: Language impairment, autism, life, animated film